2010
DOI: 10.2174/1876388x01002010040
|View full text |Cite
|
Sign up to set email alerts
|

Is there Still a Place for Perfusion SPECT in the Diagnosis of Dementia?

Abstract: Abstract:Although research interest within functional imaging has moved towards applications of MRI, such as BOLD and perfusion imaging, there is a wealth of clinical experience in emission tomographic imaging techniques that make the use of these modalities relevant for the decades to come. This review touches upon the technical and practical issues that distinguish SPECT from PET, describes perfusion and metabolic changes observed in the dementias, compares the clinical utility of the two techniques, and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 82 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…AD starts with posterior cingulate or medial temporal hypoperfusion, followed by bilateral posterior temporoparietal hypoperfusion . Later, prefrontal hypoperfusion appears.…”
Section: Introductionmentioning
confidence: 99%
“…AD starts with posterior cingulate or medial temporal hypoperfusion, followed by bilateral posterior temporoparietal hypoperfusion . Later, prefrontal hypoperfusion appears.…”
Section: Introductionmentioning
confidence: 99%
“…Two SPECT studies in patients with pathological diagnoses of AD reported sensitivities of 86 and 63%, and specificities of 73 and 93%, respectively [32,33]. Ebmeier [34 ]concluded that SPECT and PET are equally sensitive in aiding the differential diagnosis of dementia in challenging cases, with SPECT having the additional benefit of being the less costly than PET [35]. …”
Section: Discussionmentioning
confidence: 99%
“…Opinions still differ on whether PET or SPECT is more useful to aid diagnosis (Ishii and Minoshima, 2005;Lucignani and Nobili, 2010;Pupi and Nobili, 2005). Some reviews have also found in favour of PET (Devous, 2002;Silverman, 2004), with others finding both PET and SPECT to be useful to help differentiate dementia diagnoses (Ebmeier, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of SPECT and PET in those with MCI have increasingly been carried out to examine whether such imaging techniques can predict the progression to dementia. These can be difficult to design and interpret Bloudek ( with MCI being a heterogeneous group with variable progression; also, the gold standard autopsy confirmed that studies are difficult because of the often long period between diagnosis and death (Ebmeier, 2010). The only head-to-head study carried out has already been mentioned (Dobert et al, 2005).…”
Section: Spect/pet In Mild Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation